Unravelling the Diversity of Microorganisms in Ticks from Australian Wildlife - Ghafar, Abdul; Davies, Nick; Tadepalli, Mythili; Breidahl, Amanda; Death, Clare; Haros, Philip; Li, Yuting; Dann, Peter; Cabezas-Cruz, Alejandro; Moutailler, Sara; Foucault-Simonin, Angélique; Gauci, Charles G.; et al. (Pathogens (Basel), 2023)
Ticks and tick-borne pathogens pose a significant threat to the health and welfare of humans and animals. Our knowledge about pathogens carried by ticks of Australian wildlife is limited. This study aimed to characterise ticks and tick-borne microorganisms from a range of wildlife species across six sites in Victoria, Australia. Following morphological and molecular characterisation (targeting 16S rRNA and cytochrome c oxidase I), tick DNA extracts (n = 140) were subjected to microfluidic real-time PCR-based screening for the detection of microorganisms and Rickettsia-specific real-time qPCRs. Five species of ixodid ticks were identified, including Aponomma auruginans, Ixodes (I.) antechini, I. kohlsi, I. tasmani and I. trichosuri. Phylogenetic analyses of 16S rRNA sequences of I. tasmani revealed two subclades, indicating a potential cryptic species. The microfluidic real-time PCR detected seven different microorganisms as a single (in 13/45 ticks) or multiple infections (27/45). The most common microorganisms detected were Apicomplexa (84.4%, 38/45) followed by Rickettsia sp. (55.6%, 25/45), Theileria sp. (22.2% 10/45), Bartonella sp. (17.8%, 8/45), Coxiella-like sp. (6.7%, 3/45), Hepatozoon sp. (2.2%, 1/45), and Ehrlichia sp. (2.2%, 1/45). Phylogenetic analyses of four Rickettsia loci showed that the Rickettsia isolates detected herein potentially belonged to a novel species of Rickettsia. This study demonstrated that ticks of Australian wildlife carry a diverse array of microorganisms. Given the direct and indirect human–wildlife–livestock interactions, there is a need to adopt a One Health approach for continuous surveillance of tick-associated pathogens/microorganisms to minimise the associated threats to animal and human health.